2005
DOI: 10.5014/ajot.59.4.377
|View full text |Cite
|
Sign up to set email alerts
|

Vision, Visual-Information Processing, and Academic Performance Among Seventh-Grade Schoolchildren: A More Significant Relationship Than We Thought?

Abstract: Visual function significantly distinguishes between children with and without mild academic problems, as well as on visual-perception scores. The high occurrence of visual deficits among participants warrants consideration of vision deficits among schoolchildren with academic performance difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 39 publications
5
60
0
3
Order By: Relevance
“…This visual processing deficit has been interpreted as strictly connected to the reading impairment due to the limitation of the ability of the visual-attention window to spread over a whole word, and then to identify words with fast and parallel procedures. As regards to VMI task, in the older subgroup with DD, our results are consistent with those reported by Goldstand et al (2005), that failed to find differences in visual processing between NR and children with DD.…”
Section: Discussionsupporting
confidence: 92%
“…This visual processing deficit has been interpreted as strictly connected to the reading impairment due to the limitation of the ability of the visual-attention window to spread over a whole word, and then to identify words with fast and parallel procedures. As regards to VMI task, in the older subgroup with DD, our results are consistent with those reported by Goldstand et al (2005), that failed to find differences in visual processing between NR and children with DD.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are comparable with previous reports suggesting that children with visual function anomalies could be at disadvantage in reading, writing and academic performance [5,12,13,25,[29][30][31][32][33][34]. Some studies support the possibility that children with unstable binocular control commit more phonological spelling errors, even when age, IQ and phonemic awareness were taken into account [29].…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies concluded that as a child progresses through school, the relationship between vision and reading changes, with the role of vision being more significant among younger children in the early school grades [3,30].…”
Section: Discussionmentioning
confidence: 99%
“…(Fulk & Goss, 2001; Goldstand, Koslowe, & Parush, 2005; Johnson, Nottingham, Strutton, & Zaba, 1996; Krumholtz, 2000; Kulp & Schmidt, 1996; Maples, 2003; Mathers, Keyes, & Wright, 2010; Shin, Park, & Park, 2009; Vaughn, Maples, & Hoenes, 2006) Given that academic achievement is one of the most powerful predictors of lifelong health,(Egerter, 2009; Freudenberg & Ruglis, 2007; Topitzes, Godes, Mersky, Ceglarek, & Reynolds, 2009) addressing factors that contribute to poor school function may be critical to resolving health disparities. However, while one might predict that access to corrective lenses improves school function and overall child health, there is surprisingly little scientific evidence supporting this assumption.…”
Section: Objectivesmentioning
confidence: 99%